Variations in Mediterranean–Atlantic exchange across the late Pliocene climate transition - Á. García-Gallardo; P. Grunert; W. E. Piller (Climate of the Past, 2018)
Mediterranean–Atlantic exchange through the Strait of Gibraltar plays a significant role in the global ocean–climate dynamics in two ways. On one side, the injection of the saline and warm Mediterranean Outflow Water (MOW) contributes to North Atlantic deep-water formation. In return, the Atlantic inflow is considered a sink of less saline water for the North Atlantic Ocean. However, while the history of MOW is the focus of numerous studies, the Pliocene Atlantic inflow has received little attention so far. The present study provides an assessment of the Mediterranean–Atlantic exchange with a focus on the Atlantic inflow strength and its response to regional and global climate from 3.33 to 2.60 Ma. This time interval comprises the mid-Pliocene warm period (MPWP; 3.29–2.97 Ma) and the onset of the Northern Hemisphere glaciation (NHG). For this purpose, gradients in surface δ 18 O records of the planktonic foraminifer Globigerinoides ruber between the Integrated Ocean Drilling Program (IODP) Hole U1389E (Gulf of Cádiz) and Ocean Drilling Program (ODP) Hole 978A (Alboran Sea) have been evaluated. Interglacial stages and warm glacials of the MPWP revealed steep and reversed (relative to the present) W–E δ 18 O gradients suggesting a weakening of Mediterranean–Atlantic exchange likely caused by high levels of relative humidity in the Mediterranean region. In contrast, periods of stronger inflow are indicated by flat δ 18 O gradients due to more intense arid conditions during the severe glacial Marine Isotope Stage (MIS) M2 and the initiation of NHG (MIS G22, G14, G6–104). Intensified Mediterranean–Atlantic exchange in cold periods is linked to the occurrence of ice-rafted debris (IRD) at low latitudes and a weakening of the Atlantic Meridional Overturning Circulation (AMOC). Our results thus suggest the development of a negative feedback between AMOC and exchange rates at the Strait of Gibraltar in the latest Pliocene as it has been proposed for the late Quaternary.